STRATEGI ALTERNATIF ASPEK PEMASARAN PADA UMKM BATIK VIRDES - Maulana, Akbar; Dwi Wulan Anggraini; Ribi Ayu Budi S; Ali Sistani Habsah; Jemi Cahya Adi Wijaya (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2025)
Banyuwangi is well known as a region rich in cultural heritage, one of which is batik with its distinctive Gajah Oling motif that holds aesthetic, philosophical, and spiritual values. One of the small enterprises that contributes to preserving this cultural heritage is Batik Virdes, located in Tampo Village—a batik village that serves as a cultural tourism destination for both domestic and international visitors. This study aims to assess the feasibility of Batik Virdes from a marketing aspect, considering the vital role marketing plays in the sustainability and growth of UMKM. Based on the feasibility analysis, Batik Virdes holds strong competitive advantages in its unique and diverse batik motifs, along with high customer loyalty as shown by the 40–50% repeat purchase rate. Although 25% of customers reported dissatisfaction, this issue can still be resolved through product improvement. The analysis suggests that Batik Virdes should adopt a more progressive and bold marketing approach by leveraging its strengths and maximizing market opportunities. Recommended strategies include expanding promotional efforts through digital and traditional media, developing products aligned with current consumer trends, strengthening brand identity through the creation of an official slogan, and expanding distribution networks through strategic partnerships. The findings of this study are expected to provide valuable insights for Batik Virdes in developing effective marketing strategies, thereby increasing competitiveness and reinforcing its position in both local and national batik markets.